Mirron wardrobe - technology blueprint / Amirul Hakim Rusdi... [et al.] - Rusdi, Amirul Hakim; Zainal Abidin, Muhammad Hariz Zafran; Kamaruddin, Fatin Nurul Atikah; Zalman Iswandi, Muhammad Haziq Haikal; Mohd Khir, Muhammad Nur Akmal (2019)
The latest technology of NAQ'S TECH output in combining the iron board, mirror, and makeup table. Name of this product is Mirror Wardrobe. The product combination of these three components is able to facilitate and speed up customer self preparation with one objective: to make them accessible to all. It all started when its founder collaborated with an Malaysian engineer. One made beauty for the Mirror Wardrobe is, the other cherished an ideal: to make a technology, which until then had been exclusively for professionals, accessible to everyone. This company brand's first invention was an ironing board incorporating a professional steam generator guaranteeing unparalleled results and ultimate ease of use within your home. It was an immediate and enduring success. NAQ'S TECH ironing,systems are designed with a single goal: to help you obtain a unique, professional result within your home. To do this, the brand brought together an exclusive active board, equipped with a quality mirror and material system, an integrated professional steam generator and a professional iron.